The WHO Framework Convention on Tobacco Control - time for a civil society equivalent? - Mike Daube (Sax Institute, 2020)
rticle 5.3 of the World Health Organization (WHO) Framework Convention on Tobacco Control (FCTC) requires that: "In setting and implementing their public health policies with respect to tobacco control, Parties shall act to protect these policies from commercial and other vested interests of the tobacco industry in accordance with national law." While this sets clear standards for governments, there is no equivalent for health and related organisations and those who work with them. The tobacco industry, now more than ever, seeks the credibility of association with reputable scientists and organisations, as part of a strategy to present itself as part of the solution to a problem it has created and continues to promote. At the same time, it opposes evidence-based action to reduce smoking and its harms. This paper proposes that it is time to establish a civil society equivalent of Article 5.3 to protect reputable organisations from associating with or lending support and credibility to the tobacco industry.